Targeted treatment for chronic lymphocytic leukemia: clinical potential of obinutuzumab - Smolej L (Dove Medical Press, 2014)
Lukáš Smolej 4th Department of Internal Medicine – Hematology, University Hospital Hradec Králové and Charles University in Prague, Faculty of Medicine in Hradec Králové, Hradec Králové, Czech Republic Abstract: Introduction of targeted agents revolutionized the treatment of chronic lymphocytic leukemia (CLL) in the past decade. Addition of chimeric monoclonal anti-CD20 antibody rituximab to chemotherapy significantly improved efficacy including overall survival (OS) in untreated fit patients; humanized anti-CD52 antibody alemtuzumab and fully human anti-CD20 antibody ofatumumab lead to improvement in refractory disease. Novel small molecule inhibitors such as ibrutinib and idelalisib demonstrated excellent activity and were very recently licensed in relapsed/refractory CLL. Obinutuzumab (GA101) is the newest monoclonal antibody approved for the treatment of CLL. This novel, glycoengineered, type II humanized anti-CD20 antibody is characterized by enhanced antibody-dependent cellular cytotoxicity and direct induction of cell death compared to type I antibodies. Combination of obinutuzumab and chlorambucil yielded significantly better OS in comparison to chlorambucil monotherapy in untreated comorbid patients. These results led to approval of obinuzutumab for the treatment of CLL. Numerous clinical trials combining obinutuzumab with other cytotoxic drugs and novel small molecules are currently under way. This review focuses on the role of obinutuzumab in the treatment of CLL. Keywords: chronic lymphocytic leukemia, anti-CD20 antibodies, chlorambucil, rituximab, ofatumumab, obinutuzumab, overall survival